2018
DOI: 10.1016/j.foodcont.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Listeria spp. and characterization of Listeria monocytogenes isolated from food products in Tetouan, Morocco

Abstract: A total of 1096 food samples were purchased in Tetouan, North-Western of Morocco, to examine the presence of Listeria spp. Eighty (7.3%) of the tested samples were found positive for the presence of Listeria spp., while L. monocytogenes was detected in 16 (1.5%) samples.L. monocytogenes isolates belonged to clonal complexes CC2 (PCR serogroup IVb) and CC199 (PCR serogroup IIa) and to 8 different combined AscI/ApaI pulsed-field gel electrophoresis profiles. Core genome multilocus sequence typing (cgMLST) allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 29 publications
5
30
4
2
Order By: Relevance
“…Major epidemics of listeriosis occur because of serotype 4b strains [21]; however, there was only one strain within this serogroup in this study. In another study [51], 16 L. monocytogenes strains from food samples were found to belong to serogroup IVb (87.5%) within phylogenetic lineage I and serogroup IIa belonging to phylogenetic lineage II (12.5%). Similar to the findings of this study, predominant serogroup in their study was serogroup IIa.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Major epidemics of listeriosis occur because of serotype 4b strains [21]; however, there was only one strain within this serogroup in this study. In another study [51], 16 L. monocytogenes strains from food samples were found to belong to serogroup IVb (87.5%) within phylogenetic lineage I and serogroup IIa belonging to phylogenetic lineage II (12.5%). Similar to the findings of this study, predominant serogroup in their study was serogroup IIa.…”
Section: Resultsmentioning
confidence: 93%
“…In the related literature, the reported prevalence rates of this bacterium in poultry meat products were 3.7% in Morocco [45], 8.9% in Algeria [46], 15.3% in Romania [47], 17.9% in Brazil [44], 38% in Greece [12], 2.1% [48], 45% in Turkey [49], and 58% in Brazil [50]. The differences in the prevalence may be due to the differences in geographical characteristics, sampling strategies, hygienic conditions, and microbiological analysis methods [51]. L. monocytogenes contamination of poultry meat may occur during production, processing, and storage [44].…”
Section: Resultsmentioning
confidence: 99%
“…ST20 strains, also represented by five isolates, appear to be rare, and rather environmentally associated, especially to silage and animals [ 32 ]. Interestingly, ST199, originating in this study from a meat product in Morocco, was also present in legally sold Moroccan food products (2009–2015) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, Amajoud et al. () reported that all 16 food L. monocytogenes isolates were susceptible to penicillin G, chloramphenicol, rifampicin, streptomycin, vancomycin, fusidic acid, trimethoprim, levofloxacin, moxifloxacin, ciprofloxacin, erythromycin, amikacin, kanamycin, amoxicillin, ampicillin, gentamicin, imipenem, and tobramycin. However, all isolates showed resistance to cefotaxime, sulfonamide, nalidixic acid, fosfomycine, and lincosamide.…”
Section: Prevalence Of Antibiotic Resistance Among Food Isolates Of Lmentioning
confidence: 99%